QUANTIFICATION OF THE KAERI'S MOVABLE NEUTRON IRRADIATOR BY USING A 6LiI(Eu) SCINTILLATOR. Issue 3 (17th June 2019) - Lee, Seung Kyu; Kim, Sang In; Lee, Jungil; Chang, Insu; Kim, Jang-Lyul; Kim, Hyoungtaek; Kim, Min Chae; Kim, Bong-Hwan
Abstract: There is no standardised on-site calibration system for performance testing and calibration of neutron area monitors although there is a mobile irradiation device as like a neutron howitzer. For this reason, neutron area monitors, which legally and periodically require calibration in Korea, are removed from the installation location and tested at the Korea Atomic Energy Research Institute (KAERI) or the Korea Research Institute of Standards and Science (KRISS). To test the possibility of an on-site performance calibration system, the KAERI manufactured a movable neutron irradiator. The movable neutron irradiator is composed of high-density polyethylene and has an overall size of 50 cm (L) × 50 cm (W) × 46 cm (H). In this study, the neutron fields generated by the movable neutron irradiator were quantified at distances of 80, 100, 120, and 140 cm from the centre of the source. Quantification was performed using the initially estimated neutron spectrum from the computer simulation, the count rate data measured using a 6 LiI(Eu) scintillator combined with a Bonner sphere spectrometer (BSS), and the response function of the BSS. As a result of the quantification of the neutron field at each distance, the fractions of scattered neutrons to total neutron fluence were almost constant within 5%.